Wireless monitoring system and controlling software for smart greenhouse management - Jafar, Imran Bin; Raihana, Kanij; Bhowmik, Sujan; Shakil, Shifur Rahman (© 2014 IEEE Computer Society, 2016)
This conference paper was presented in the 2014 International Conference on Informatics, Electronics and Vision, ICIEV 2014; Dhaka; Bangladesh; 23 May 2014 through 24 May 2014 [© 2014 IEEE Computer Society] The conference paper's definite version is available at: http://10.1109/ICIEV.2014.6850748